1997
DOI: 10.2307/3545809
|View full text |Cite
|
Sign up to set email alerts
|

The Moran Effect and Synchrony in Population Dynamics

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
236
2
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 281 publications
(251 citation statements)
references
References 46 publications
10
236
2
3
Order By: Relevance
“…The central idea of the Moran effect is that natural communities would be synchronized if they were subjected to regional drivers (Ranta et al 1997;Hudson and Cattadori 1999;Ripa 2000). Following the theory of the Moran effect, the causes of synchrony for population dynamics have been documented extensively in most of the published literatures.…”
Section: Discussionmentioning
confidence: 99%
“…The central idea of the Moran effect is that natural communities would be synchronized if they were subjected to regional drivers (Ranta et al 1997;Hudson and Cattadori 1999;Ripa 2000). Following the theory of the Moran effect, the causes of synchrony for population dynamics have been documented extensively in most of the published literatures.…”
Section: Discussionmentioning
confidence: 99%
“…First, as the frequency and severity of the densityindependent perturbations have changed, they now occur too frequently and/or are too strong to sustain periodic oscillations (Lindström et al 1995;Ranta et al 1997a;Cattadori et al 2005). Ranta et al (1997b) showed for different types of dynamics that increasing frequency and strength of the Moran effect may lead to loss of cyclic components.…”
Section: Discussionmentioning
confidence: 99%
“…in McKone et al (1998)). The Moran Effect or synchronisation using weather cues (Ranta et al 1997;Kelly et al 2013) could also account for this non-linear effect of weather variability and seed production. These exosomatic signals may act as triggers for mobilising stored reserves in plants to produce seeds.…”
Section: Rethinking the Influence Of Weather On Masting Behaviourmentioning
confidence: 99%